'I just need an opiate refill to get me through the weekend'. Issue 4 (22nd February 2019) - Yan, Eric; Kuo, Dennis John
Abstract : In this article, we discuss the ethical dimensions for the prescribing behaviours of opioids for a chronic pain patient, a scenario commonly witnessed by many physicians. The opioid epidemic in the USA and Canada is well known, existing since the late 1990s, and individuals are suffering and dying as a result of the easy availability of prescription opioids. More recently, this problem has been seen outside of North America affecting individuals at similar rates in Australia and Europe. We argue that physicians are also confronted with an ethical crisis where a capitalist-consumerist society is contributing to this opioid crisis in which societal, legal and business interests push physicians to overprescribe opioids. Individual physicians often find themselves unequipped and unsupported in attempts to curb the prescribing of opioid medications and balance competing goals of alleviating pain against the judicious use of pain medications. Physicians, individually and as a community, must reclaim the ethical mantle of our profession, through a more nuanced understanding of autonomy and beneficence. Furthermore, physicians and the medical community at large have a fiduciary duty to patients and society to play a more active role in curbing the widespread distribution of opioids in our communities.